(untitled) (The International Journal for Scientific Research, 2024)
This study aimed to analyze the role of internal control, specifically its dimensions (internal control environment, control activities, and risk assessment), in enhancing the financial performance at King Saud Medical City in Riyadh. The research was conducted within the medical services sector, focusing on evaluating the effectiveness of the current internal control system in the city and its impact on achieving financial and administrative objectives. The study adopted a descriptive-analytical approach, collecting data through questionnaires administered to officials and employees at King Saud Medical City. The data were analyzed using appropriate statistical methods to identify the relationships and impacts between internal control components and financial performance. The study found a statistically significant positive relationship between the effectiveness of the internal control system and the improvement of financial performance at King Saud Medical City. The findings revealed that the implementation of effective internal control procedures significantly contributes to reducing financial waste, enhancing the efficiency of financial operations, and achieving desired financial goals. The study recommended strengthening the internal control system at King Saud Medical City by developing more rigorous and comprehensive control policies and procedures. It also suggested training employees on the importance of internal control and its role in improving financial performance, as well as implementing modern techniques in financial control to enhance system effectiveness and achieve better outcomes.